Obsessive-Compulsive Disorder as a Disturbance of Security Motivation. - Szechtman H; Woody E (American Psychological Association (APA), 2004)
The authors hypothesize that the symptoms of obsessive-compulsive disorder (OCD), despite their apparent nonrationality, have what might be termed an epistemic origin--that is, they stem from an inability to generate the normal "feeling of knowing" that would otherwise signal task completion and terminate the expression of a security motivational system. The authors compare their satiety-signal construct, which they term yedasentience, to various other senses of the feeling of knowing and indicate why OCD-like symptoms would stem from the abnormal absence of such a terminator emotion. In addition, they advance a tentative neuropsychological model to explain its underpinnings. The proposed model integrates many previous disparate observations and concepts about OCD and embeds it within the broader understanding of normal motivation.
Keywords: Affect; Animals; Cues; Humans; Internal-External Control; Knowledge; Models, Psychological; Motivation; Obsessive-Compulsive Disorder; Reality Testing; Satiety Response